Risk and prevalence of Relative Energy Deficiency in Sport (REDs) among professional female football players - Dasa, M. S.; Friborg, O.; Kristoffersen, M.; Pettersen, G.; Sagen, J. V.; Torstveit, M. K.; Sundgot-Borgen, J.; Rosenvinge, J. H. (European Journal of Sport Science, 2024)
A high prevalence of low energy availability (LEA) has been reported in female football players. This is of concern as problematic LEA may evolve into a syndromic pattern known as relative energy deficiency in sport (REDs). Given the difficulties in accurately assessing LEA, our study shifts emphasis to measurable indicators of REDs, serving as proxies for health detriments caused by LEA. The present cross-sectional study aimed to quantify the risk of REDs and to assess the prevalence of indicators indicative of the syndrome. 60 players (tiers 3 and 4) from three Norwegian football teams were analyzed as a single cohort but also stratified based on player position and menstrual status. The proportion of players at risk for REDs was 22%, that is, 17% with mild, 3% with moderate to high, and 2% with very high/extreme risk, respectively. The majority of the cohort (71%) presented with no primary indicators, while 20%, 7%, and 2% presented with one, two, and three primary indicators, respectively. Regarding secondary indicators, 57% had none, 33% had one, and 10% had two indicators. For associated indicators, 30% had none, 42% had one, 18% had two, 8% had three, and 2% had four indicators. Player position did not affect the prevalence of REDs indicators. Among noncontraceptive users (n = 27), secondary amenorrhea (AME) was reported by 30%. These findings indicate that health and performance teams should prioritize universal health promoting strategies rather than selective or indicative strategies. Particularly, focus on nutritional periodization to secure sufficient energy availability, mitigating the risk of problematic LEA and REDs should be addressed.